2017
DOI: 10.3892/etm.2017.5156
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin augments activation of liver regeneration through attenuating transforming growth factor‑β1 induced‑apoptosis in obstructive jaundice rats

Abstract: Obstructive jaundice, owing to biliary obstruction, has been illustrated to trigger various biochemical, histological and immunological changes, leading to liver damage or even failure. The detailed molecular mechanism of simvastatin (Sim) involvement in liver regeneration during obstructive jaundice progression remains poorly elucidated. In the present study, an acute obstructive jaundice rat model was established by ligation and division of common bile duct, which was used to investigate the effects of Sim a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In the current study, we observed increased TGFβ1 expression localized primarily to hepatocyte populations due to its co-localization with CK8, supporting findings from our previous work demonstrating TGFβ1 co-localization> with albumin during AOM-induced liver failure [12]. Possible consequences of TGFβ1 signaling in hepatocytes may range from induction of apoptotic pathways [31] to the inhibition of hepatocyte proliferation and liver regeneration [29]. In the current study, we have demonstrated that anti-TGFβ1 treatment had similar liver pathology after injection of AOM compared to IgG1 control mice, but had protective effects on the neurological complications associated with acute liver failure.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, we observed increased TGFβ1 expression localized primarily to hepatocyte populations due to its co-localization with CK8, supporting findings from our previous work demonstrating TGFβ1 co-localization> with albumin during AOM-induced liver failure [12]. Possible consequences of TGFβ1 signaling in hepatocytes may range from induction of apoptotic pathways [31] to the inhibition of hepatocyte proliferation and liver regeneration [29]. In the current study, we have demonstrated that anti-TGFβ1 treatment had similar liver pathology after injection of AOM compared to IgG1 control mice, but had protective effects on the neurological complications associated with acute liver failure.…”
Section: Discussionsupporting
confidence: 88%
“…However, the specific mechanism of hepatic injury caused by OJ remains not fully elucidated. An abnormal increase in hepatocyte apoptosis is currently considered to be the pathogenesis of hepatic atrophy caused by OJ (4,5). It has been reported that, due to endotoxin stimulation during OJ, Kupffer cells secrete a large number of inflammatory factors, such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), which induce hepatocyte apoptosis (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, simvastatin has liver regeneration capability during obstructive jaundice progression and exerts hepatoprotective effects on liver cells via upregulation of Smad7 expression and impaired TGF-β signaling. The expression of hepatic TGF-β1 and Smad3 are augmented during bile duct ligation (Fang et al, 2017). Besides, bone morphogenetic protein (BMP)-9, a member of TGF-β superfamily is constitutively produced in the hepatocytes.…”
Section: Nf-κb Signalingmentioning
confidence: 99%
“…Following ligand binding with cell surface receptors, Smads are phosphorylated then they associate with Smad4 and translocate into the nucleus to regulate the expression of the target gene. In contrast, Smad signaling is negatively regulated by Smad7 (Fang, He, & Luan, 2017). The studies have revealed that TGF-β is implicated in many kinds of CLD.…”
Section: Nf-κb Signalingmentioning
confidence: 99%